Generation of red-NIR bi-modal fluorescence in hybrid nanostructure - Singh P.; Singh S.K.; Singh P.; Prakash R.; Rai S.B. (My University, 2025)
We have developed an ultrafine (<15 nm) hybrid nanoparticle (HNPs) consisting of lanthanide doped upconversion nanoparticles (UCNPs, NaY0.797Tm0.003Yb0.2F4), manganese doped zinc selenide quantum dots-(QDs, Mn:ZnSe) and silver nanoparticles (AgNPs). Synthesized HNPs involves electrostatic interaction among constituent particles. Thus, the coupling among constituent particles is relatively more strong contrary to the usual weak Van der Waals force based HNPs. HNPs emit nearly pure red-NIR emission both through normal fluorescence (under UV light excitation) and through photon upconversion process (under NIR excitation). AgNPs act as an optical filter for blue emission both for- (i) band to band transition of ZnSe and (ii) UC emission of Tm3+ ions (1G4→3H6) and thus turns the overall emission color to be in red-NIR region. Decay time measurement probes that, quenching of blue emission bands are primarily due to resonance energy transfer from UCNPs and QDs to the AgNPs (40 μL) with an energy transfer efficiency of 36% and 70%, respectively. These ultrafine and bimodal emitting HNPs could be suitable as optical imaging probe, in first biological window, and for other optoelectronic applications. © 2019 Elsevier Ltd